The role of TRP ion channels in migraine and headache. (18th January 2022) - Iannone, Luigi Francesco; De Logu, Francesco; Geppetti, Pierangelo; De Cesaris, Francesco
Highlights: The transient receptor potential (TRP) channel family comprise more than 50 members. Thermo-TRPs were proposed to contribute in transmission/modulation of nociception. TRPA1 and TRPV4 have been identified also in non-neuronal cells. TRP stimulation release CGRP, activated or sensitized by endogenous/exogenous stimuli. TRP channels, and mainly TRPA1, could be involved in migraine pathophysiology. TRP targeting may be proposed as new targets for therapy. Abstract: Migraine afflicts more than 10% of the general population. Although its mechanism is poorly understood, recent preclinical and clinical evidence has identified calcitonin gene related peptide (CGRP) as a major mediator of migraine pain. CGRP, which is predominantly expressed in a subset of primary sensory neurons, including trigeminal afferents, when released from peripheral terminals of nociceptors, elicits arteriolar vasodilation and mechanical allodynia, a hallmark of migraine attack. Transient receptor potential (TRP) channels include several cationic channels with pleiotropic functions and ubiquitous distribution in various cells and tissues. Some members of the TRP channel family, such as the ankyrin 1 (TRPA1), vanilloid 1 and 4 (TRPV1 and TRPV4, respectively), and TRPM3, are abundantly expressed in primary sensory neurons and are recognized as sensors of chemical-, heat- and mechanical-induced pain, and play a primary role in several models of pain diseases, including inflammatory, neuropathic cancer pain, and migraine pain. In addition, TRP channel stimulation results in CGRP release, which can be activated or sensitized by various endogenous and exogenous stimuli, some of which have been proven to trigger or worsen migraine attacks. Moreover, some antimigraine medications seem to act through TRPA1 antagonism. Here we review the preclinical and clinical evidence that highlights the role of TRP channels, and mainly TRPA1, in migraine pathophysiology and may be proposed as new targets for its treatment.